La Abundancia de Recursos Naturales y el Crecimiento Económico en América Latina - Fernández Cadena, Mario Andrés (2005)
Attempts to explain the poor economic performance of natural resource rich countries abound. Institutional arrangements, performance of domestic markets and credit constraints have been mentioned as likely reasons of the deceptive growth in Latin America. In fact, this paper investigates the so-called Natural Resource Curse in 26 Latin American Countries on a panel ranging from 1980 to 2000, where the proxy variable for resource abundance is the Value Added of the primary sectors to GDP. Through a simple econometric specification, the channels of operation of the resource curse are shown, through which a total resource effect is computed. The main result, a direct negative effect from natural resources to economic growth, is robust to the introduction of new features to the simple model and the application of different estimation methods (Within Groups in the recursive panel and Three Stage Least Squares in the equations system).